Bahasa inggris - Lina Saptaria; Nurali Agus Najibul Zamzam (LPPM UIKA Bogor, 2022)
The purpose of this study was to examine the effect of quality, design, and price on purchasing decisions of furniture products partially and simultaneously. The population in this study were all customers of Jati Indah Furniture. The research sample was taken using a purposive sampling technique. The number of samples is 38 respondents. Data collection techniques using questionnaires, observations, and interviews. Data analysis used classical assumption tests, multiple linear regression tests, and hypothesis testing. The value of the multiple linear regression equation is Y = 0.715 + 1.060(X1) + 0.108(X2) + (0.199)(X3). The results of this study indicate that: (1) product quality has a positive and significant effect on purchasing decisions for furniture products; (2) product design has a positive and significant effect on purchasing decisions for furniture products; (3) product prices have a positive and significant effect on purchasing decisions for furniture products; (4) quality, design, and price have a significant effect on purchasing decisions for furniture products; The implication of the results of this study is to provide managerial information, especially on the marketing aspect of furniture products. The results of this study can be used as the basis for making decisions by the manager of Jati Indah Furniture about the variables that influence purchasing decisions for furniture products, namely: product quality, product design, and product price. Suggestions for further researchers are to examine other variables that might influence the decision to purchase furniture products such as promotion, product innovation, service quality, and consumer trust.